Efektivitas Program Pelatihan di Dinas Transmigrasi dan Tenaga Kerja bagi Pemanfaatan Keilmuan Sumber Daya Manusia - Indah Levina; Sudarman Sudarman (Pencerah, 2021)
This research aims to explain the effectiveness of human resource development, training effectiveness, training benefits, inhibiting factors, supporting factors, and the effectiveness of post-training human resource scientific utilization at the office of Transmigration and Labor (DISTRANAKER), especially in the Technical Implementation Unit, Work Training Center area. The method used in this research is a qualitative method with the techniques of data collection were documentation, observation, and interviews. This study concluded that the implementation of human resource development activities is carried out based on the effectiveness of the use of scientific human resources as well as the need for abilities and skills that are job requirements owned by each individual in accordance with their respective vocational fields. The benefits of training and development have a very good impact on human resources or training participants who want to sharpen their abilities. Training and development activities aim to increase the potential of the trainees while participating in training and development activities at the Job Training Center. The participants get an opportunity to open a personal business or get a good job at an existing agency or company in the future and must also be in accordance with with skills that have been sharpened during the training activities. The inhibiting factors obtained are the lack of attention from the office of Transmigration and Labor in the existing facilities in several vocational fields in training and also the lack of proper use of time from instructors in certain vocational fields.